Former Ratonian makes big hit as professional baseball trainer - Bogaczyk, Jack (Raton, New Mexico Raton Daily Range, 1989)
Newspaper article on former Raton resident making it as a professional baseball trainer for the Salem Buccaneers.
Master List item # 4
File location is in the Raton File Cabinet
Keywords: Sandoval, Mike; Harris, Robert; Hartman, Ed; Duncan, Chip; Bridges, Rocky; Carter, Steve; Crowley, Terry; Raton High School; New Mexico State University; Local History; Baseball; Baseball Trainer; Raton, New Mexico; Watertown, New York; Princeton, West Virginia; Pittsburgh